Hierarki Kehidupan Tumbuhan dalam Al-Qur’an: Analisis Interpretasi Zaghlul an-Najjar - Ica Fauziah Husnaini (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The phenomenon of growth in plants if traced in the explanation of the Qur'anic verse produces a wide variety of interpretations from the mufasir this is due to the different social context and scientific context, so that the focus of emphasis of what is interpreted is affected, as well as interpreting verses related to science. Mufasirs who have a scientific background in science will certainly focus more on science verses. One of them, as done by Zaghlul an-Najjar. Therefore, this study aims to explain and describe the hierarchy of plant life in the Qur'an according to the interpretation of Zaghlul an-Najjar. By looking at the growth and development of plants. In addition, researchers are also looking for stages of growth in trees. This type of research is literature with data analysis techniques used is content analysis. The collection of library materials and the object of discussion are studied coherently and then re-examined between one another with a predetermined framework. In this study Zaghlul an-Najjar describes in detail the growth and development of plants based on their parts.